Real‐World Adherence and Persistence with Direct Oral Anticoagulants in Adults with Atrial Fibrillation. Issue 10 (6th September 2017) - Manzoor, Beenish S.; Lee, Todd A.; Sharp, Lisa K.; Walton, Surrey M.; Galanter, William L.; Nutescu, Edith A.
Abstract : Background: Evidence of adherence and persistence patterns in anticoagulation (AC) therapy comparing treatment‐naïve and non‐naïve patients is lacking. The objective of this study was to evaluate patterns of medication adherence and persistence in a real‐world setting among AC‐naïve and AC‐experienced patients with atrial fibrillation (AF) who were treated with direct oral anticoagulants (DOACs). Methods: AF patients newly initiating a DOAC with a minimum of 6 months of continuous health plan enrollment pre and postindex date (first DOAC prescription) were identified from the Truven Health MarketScan Commercial and Medicare Supplemental databases (2009–2013). DOAC adherence (proportion of days covered [PDC]), persistence, and predictors of adherence were assessed at 6 and 12 months postindex. Results: Of 66, 090 AF patients included, 46.6% (n=30, 826) were AC naïve and 53.4% (n=35, 264) were AC experienced (age: 66.9 ± 12.7 vs 70.4 ± 11.4 yrs, p<0.001; male: n=19, 132 [62.1%] vs n=21, 691 [61.5%], p=0.14, respectively). A majority of patients received dabigatran as their index DOAC (n=49, 210; 74.5%). The mean PDC in AC‐naïve versus AC‐experienced patients at 6 and 12 months of follow‐up was 72.3% versus 83.3% (p<0.001) and 63.7% versus 79.9% (p<0.001), respectively. Persistence with DOAC therapy in AC‐naïve and AC‐experienced patients at 6 and 12 months ranged from 59.3% and 76.3% (p<0.0001) to 31.6% and 50.2% (p<0.0001), respectively. Predictors of higher DOAC adherence were older age and higher number of concomitant medications. Predictors of lower adherence were higher number of comorbidities and AC‐naïve user status. Conclusion: Medication adherence and persistence with DOACs declined over time and both were suboptimal and lower (at 6 and 12 mo postindex) in AC‐naïve compared to AC‐experienced patients. These findings can help target future strategies or interventions for patient education and long‐term AC management especially in those patients naïve to DOAC therapy. Future investigation should examine potential reasons for differences in DOAC adherence and persistence between AC‐experienced versus AC‐naïve patients and the implications for patient outcomes.